Acute Allograft Rejection following Interferon Therapy for Hepatitis C in Recipients who have Returned to Dialysis after Kidney Transplant Failure: Case Study. Issue 11 (November 2014) - Fabrizi, Fabrizio; D'Ambrosio, Roberta; Pallotti, Francesco; Berardinelli, Luisa; Messa, Piergiorgio; Martin, Paul; Aghemo, Alessio
Interferon-based therapy remains the gold standard for hepatitis C in patients with chronic kidney disease; however, due to the high rate of IFN-induced rejection after transplant, treatment of HCV-infected kidney transplant recipients is recommended only in particular circumstances. We report the case of a 45-year-old Caucasian female with chronic hepatitis C (genotype 1b) who returned to hemodialysis following the complete functional loss of her kidney transplant. She started combination antiviral therapy with peg-IFN-α2a (135 mcg sc weekly) plus ribavirin (200 mg daily) nine months after the re-initiation of hemodialysis. Antiviral therapy was neither effective nor safe; ribavirin was stopped at week 38 due to hemolytic anemia; on-treatment HCV breakthrough was observed at week 48; and acute rejection occurred after four months of IFN-based therapy. Diagnosis of acute allograft rejection was suspected on the grounds of clinical, radiographic, and laboratory data. Allograft nephrectomy was then performed and histology showed acute-on-chronic rejection. This is an uncommon case of IFN-associated kidney rejection in an allograft recipient who had functional loss of her graft and had returned to hemodialysis. In view of the risk of rejection of renal allograft, and the limited efficacy of IFN-based treatment of hepatitis C, physicians should be aware of effective treatment with oral antiviral agents and avoid the use of IFN in patients on maintenance dialysis with failed renal allograft.